2013
DOI: 10.1097/aln.0b013e3182815948
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Anesthesia Impairs the Maturation and Survival of Adult-born Hippocampal Neurons

Abstract: Background: Adult neurogenesis occurs in the hippocampus of most mammals, including humans, and plays an important role in hippocampal-dependent learning. This process is highly regulated by neuronal activity and might therefore be vulnerable to anesthesia. In this article, the authors investigated this possibility by evaluating the impact of propofol anesthesia on mouse hippocampal neurons generated during adulthood, at two functionally distinct maturational stages of their development. Methods: Adult-born hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 48 publications
2
57
1
Order By: Relevance
“…First, we did not determine the dose-dependent effects of propofol on caspase-3 activation and cognitive function in the aged and AD Tg mice, because these AD Tg and aged mice are expensive and not easy to obtain. Different doses of propofol may cause neurotoxic [5456] and neuroprotective [5759] effects. It is possible that different doses of propofol may neither attenuate the caspase-3 activation nor improve the cognitive function in the aged and AD Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not determine the dose-dependent effects of propofol on caspase-3 activation and cognitive function in the aged and AD Tg mice, because these AD Tg and aged mice are expensive and not easy to obtain. Different doses of propofol may cause neurotoxic [5456] and neuroprotective [5759] effects. It is possible that different doses of propofol may neither attenuate the caspase-3 activation nor improve the cognitive function in the aged and AD Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…404 In the present study, we identified that Ang II induced (Martin et al, 2006;Miyazaki 445 et al, 2007). Further, it is indicated that its neuroprotec-446 tive effects were mediated via anti-oxidative and anti-447 apoptotic properties (Krzisch et al, 2013). In the present 448 study, we reported that MT-3 was down-regulated by 449 Ang II, suggesting that Ang II caused hippocampal (Chen et al, 2010(Chen et al, , 2011Gokcinar et al, 2013).…”
mentioning
confidence: 86%
“…It was reported that propofol impairs the 463 survival and maturation of adult-born hippocampal neu-464 rons in mice(Krzisch et al, 2013). It was also demon-465 strated that propofol induces apoptosis in developing 466 neurons in the in vitro and in vivo settings(Pearn et al, 467 2012).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…First, we did not determine the dose or time-dependent effects of propofol on Aβ levels in the brain tissues of the aged mice. Different treatments of propofol may be neurotoxic [47][48][49] or neuroprotective [50][51][52]. Therefore, it is possible that propofol treatment with different doses or administered at different times may have different effects on brain Aβ levels.…”
Section: Discussionmentioning
confidence: 99%